Heavy Metals Distribution In Water At Perai River - Sekhar, Thanesh Naidu (Universiti Sains Malaysia, 2022)
Perai River is Penang’s longest river and its largest water catchment area. It has been identified as a potential future water source to serve the state’s growing water demands. However, the quality of the river water is a major concern to water intake, which subsequently can also affect the treatment cost. This is due to the increased discharge of untreated industrial and domestic wastes directly into the river. Consequently, the river water could potentially be polluted by heavy metals, which are harmful to public health. Therefore, the main objective of this study is to assess the spatial and temporal distribution of heavy metals in the water at Perai River. In addition, the study aims to analyse the correlation between heavy metals and two important water quality index (WQI) parameters which are biochemical oxygen demand (BOD) and chemical oxygen demand (COD). In order to conduct the research, water samples were collected from 31 sampling points, which include 11 points in the main river (MR 1-11) and 20 points in the tributaries (TR 1-20). The sampling process was carried out thrice, whereby twice during the wet seasons of December 2021 and February 2022, and once during the dry season of April 2022. Laboratory tests such as Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES), BOD5 and COD tests were conducted using the water samples collected. From the ICP-OES test, the significant heavy metals present in the river water were identified to be mercury (Hg), aluminium (Al), iron (Fe) and manganese (Mn). The main sources of heavy metal pollution in the study area were identified to be the direct industrial and domestic waste discharge into the river. As concrete evidence, mercury concentration in Perai river was noticed to be in the alarming range of 0.97 – 5.66 ppm in Mak Mandin area which is a prominent industrial town in Butterworth, Penang. Besides that, the residential waste from TR 12, TR 13 and TR 14 flow directly to MR 7 causing the high cumulative distribution of iron at MR 7 (6 ppm). In terms of temporal distribution, the concentration of heavy metals was expected to be lower in the wet seasons compared to the dry seasons due to dilution during heavy rainfalls. For instance, the lowest aluminium concentration in Perai river water was recorded to be at 0 ppm in MR 8 during the wet season of February 2022. However, in some cases, the results of the heavy metals concentration obtained proved otherwise possibly due to the intentional discharge of a large amount of accumulated industrial waste during the wet seasons to reduce noticeability. As substantial proof, manganese concentration was found to be the highest (0.64 ppm) in April 2022 (dry season) and the lowest (0.06 ppm) in February 2022 (wet season). The correlations between heavy metals, BOD and COD were analysed using SPSS bivariate analyses. A very significant correlation was seen between Fe – COD, whereas a slightly significant correlation was seen between; Hg–COD, and Fe–BOD. A regression graph of COD concentration against Hg concentration was plotted since it was the only parametric pair with correlation significance. A best-fit line was drawn, interpreting that COD increases linearly with Hg.